Ethical Issues and Politics in Research for Sustainable Resource Management in Tanzania - Haulle, Evaristo (Cultural and religious studies, 2015)
Understanding Research ethics is the key for producing sound findings to guide management of resource in any community. Through in-depth interview, observation and documentary search, it was noted that most of the studies are not self-driven and lack ethical integrity. People are hired to produce report without clear and streamlined methodology. Nature of the community and the way it is organised poses challenge in acquiring information. In principle, culture of the people to expression is an important aspect in getting liable findings. The conflicts over resources in Namawala and Magaiduru villages have led to the loss of trust and rejects on researchers as they are discovered to provide villagers with false information. Some findings are fabricated to convince the donors’ interests to call for more funds for personal interests. Other decision makers would commission researcher to produce false data to suit their interests. This causes academic and researchers being classified as a tool of politician to pacify the public in order to maintain the status quo. The problem is caused by lack of sufficient research fund and understanding on the research essence, and importance of ethical consideration for good research. The situation causes multiple sided effects in the community. Generally, lack of research ethics and presence of greed politicians jeopardise resource management, peace and security. There is need to build the culture of truth and integrity for community development. Research methods need to be taught rigorously in order to build capacity in tools and principles.